2010
DOI: 10.1136/gut.2009.202101
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of Crohn's disease in a population-based cohort from Cardiff (1986-2003): a study of changes in medical treatment and surgical resection rates

Abstract: This population-based cohort shows marked changes in rates of surgery, and the reduction is independently associated with year of diagnosis, and associated temporally with increased and earlier thiopurine use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
275
5
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 358 publications
(313 citation statements)
references
References 28 publications
26
275
5
7
Order By: Relevance
“…Our study echoed the observed trends that more IM but less 5-ASA products are currently used in CD management [18][19][20][21][22] . Immunomodulators are effective maintenance medications and azathioprine has been shown to modestly lower the risk of surgery [23][24][25] .…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Our study echoed the observed trends that more IM but less 5-ASA products are currently used in CD management [18][19][20][21][22] . Immunomodulators are effective maintenance medications and azathioprine has been shown to modestly lower the risk of surgery [23][24][25] .…”
Section: Discussionsupporting
confidence: 74%
“…The recent shift in medical management of Crohn's disease has decreased the cumulative surgical rate of CD patients [15][16][17][18][19][20] . Our study echoed the observed trends that more IM but less 5-ASA products are currently used in CD management [18][19][20][21][22] .…”
Section: Discussionmentioning
confidence: 99%
“…In other population-based studies, the cumulative risk of surgery 10 years after diagnosis ranged from approximately 40 to 55 % [4][5][6]. A report published in 2010 found that the probability of intestinal surgery in Welsh patients (1986)(1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003) during the first year after diagnosis was independently related to the site(s) of involvement, use of oral steroids within the first 3 months after diagnosis, and early use of thiopurines [7].…”
Section: Epidemiologymentioning
confidence: 99%
“…Contrary to initial hypotheses, the introduction of thiopurine drugs has not reduced the likelihood of surgery [7,8]. As for the biological agents, Peyrin-Biroulet et al [9] analyzed follow-up data (median 56 months) for 296 patients with Crohn's disease diagnosed between 2000 and 2008 and found that early use of biological therapy decreased the risk of surgery significantly, whereas the reduction was much more limited with thiopurine therapy.…”
Section: Epidemiologymentioning
confidence: 99%
“…1,6,8,[12][13][14] Complicated disease is strongly associated with a requirement for surgery 15 ; therefore, knowledge of such genetic, environmental and clinical predictors may guide clinicians in developing a personalised approach for individual patients. 2,3,16 The ability to predict those who will have a more indolent disease course is also important given the range of adverse drug reactions and the cost of anti-TNF drugs. 3,17 There is a lack of data concerning which patients would benefit most from a top-down or bottom-up treatment strategy.…”
Section: Introductionmentioning
confidence: 99%